EPIDURAL STEROID INJECTION IN HERNIATED DISC AND LUMBAR CANAL STENOSIS: IS IT JUST A PLACEBO? - PAPANNA,AJAY KUMAR SHETTY (2021)
ABSTRACT Objective To study the role of epidural steroid injection (ESI) in patients with lumbar disc herniation (LDH) and lumbar canal stenosis (LCS). ESIs are regularly used to support non-operative treatment for LBP, and our anecdotal impression is that a considerable proportion of patients report substantial pain relief after ESI. Methods One thousand consecutive patients (645 patients with LDH and 355 patients with LCS) who required ESI from January-August 2018 were included. All were given the same ESI, prepared with triamcinolone (80 mg), bupivacaine (0.25%, 4 ml) and normal saline (4 ml). Patients were evaluated using the numerical rating scale (NRS) immediately after the injection, after 7 days, and after 3 months. Results The mean NRS back-pain score of the LDH-group was reduced from 5 (range: 4-8) to 4 (range: 2-7) immediately after injection, 2 (range: 1-7) after 7 days and 2 (range: 1-7) after 3 months (p-value<0.001). The mean NRS back-pain score of the LCS-group was reduced from 5 (range: 4-8) to 4 (range: 2-7) immediately after injection, 2 (range: 1-7) after 7 days and 3 (range: 1-7) after 3 months (p-value <0.001). The mean NRS leg-pain score of the LDH group was reduced from 5 (range: 4-9) to 3 (range: 3-7) immediately after injection, 1 (range: 1-6) after 7 days and 2 (range: 1-7) after 3 months (p-value <0.001). The mean NRS leg-pain score of the LCS group was reduced from 5 (range: 4-9) to 4 (range: 3-7) immediately after injection, 3 (range: 1-7) after 7 days and 2 (range 1-6) after 3 months (p-value <0.001). Conclusion ESI causes statistically significant improvement in back and leg pain in patients with LDH and LCS. However, the short and medium-term efficacy of ESI in the LCS group was lower than in the LDH group. Level of evidence IV; Prospective hospital-based study.